Miniaturized single layer ultra-thin polarization insensitive metasurface absorber - Zhen, Fajian; Liu, Yunqing; Dong, Junwei; Kong, Shiyuan; Jia, Feng; Arya, Ravi Kumar (Frontiers in Physics, 2025)
The current spatial electromagnetic environment is complex and dynamic, with electromagnetic interference and pollution growing increasingly severe. Utilizing electromagnetic wave manipulation technology to absorb and convert waste electromagnetic energy into useful energy is of great research significance. This study presents a miniaturized, single-layer ultrathin metasurface absorber (MA) featuring frequency tunability and polarization insensitivity. The proposed MA is constructed from four groups of rotationally symmetric herringbone-shaped structures, mounted on a Rogers 438 substrate with a metallic ground plane. This design ensures efficient absorption of electromagnetic waves across all polarization angles, while the absorption frequency can be adjusted by modifying the dimensions of the herringbone structures. The device demonstrates an absorption coverage angle of ±60° for incident waves at various oblique angles. Unlike conventional absorbers that incorporate discrete resistors within each independent unit, the proposed MA integrates these components into a unified system. By employing resistors to interconnect adjacent unit cells, the design forms a cohesive absorber structure, significantly reducing the total number of resistors required. Full-wave simulations demonstrate nearly perfect absorption of electromagnetic waves across diverse polarization angles. The MA is highly compact, with a unit-cell dimension of only 0.16λ × 0.16λ and an ultra-thin profile of only 0.023λ. The newly developed MA holds promising potential for applications in integrated devices, energy harvesting systems, and radar cross-section assessments.